Reconfiguring Chinese Nationalism - Leibold, J. author. aut Link
XI, 271 p.
Keywords: The first full length treatment of ethnic and national identity in early Twentieth-century China, Leibold traces the political and cultural strategies employed by Han Chinese elites in the process of incorporating, both discursively and physically, the diverse inhabitants of the last Qing dynasty into a new, homogenous national community.